EFEKTIVITAS METODE REBOZO TERHADAP PENURUNAN NYERI PINGGANG PADA IBU HAMIL TRIMESTER KE III DI BPM H KABUPATEN AGAM TAHUN 2025 - Handayani, Yellyta Ulsafitri; Amelia, Rini; Merianti, Liza (HUMAN CARE JOURNAL, 2025)
ABSTRACTLow back pain is one of the most common complaints experienced by pregnant women in the third trimester due to physiological and biomechanical changes during pregnancy. This discomfort can interfere with daily activities and reduce the overall quality of life. One non-pharmacological method that can be used to relieve low back pain is the Rebozo technique. Objective: This study aimed to determine the effectiveness of the Rebozo method in reducing low back pain in third-trimester pregnant women. Methods: This study used a quantitative approach with a quasi-experimental design, specifically a one-group pretest–posttest design. The sample consisted of 30 third-trimester pregnant women selected using purposive sampling. The level of pain was measured before and after the Rebozo intervention. Data were analyzed using a paired t-test. Results: The paired t-test showed a statistical value of 10.723 with a p-value < 0.05, indicating a significant difference in the level of pain before and after the intervention. These results demonstrate that the Rebozo technique is effective in reducing low back pain in pregnant women.Conclusion: The Rebozo technique is proven to be effective in reducing low back pain in third-trimester pregnant women and can be recommended as a non-pharmacological intervention within antenatal care services.Keywords: Low back pain, pregnant women, third trimester, Rebozo technique, quasi-experiment